2020
DOI: 10.1108/jrf-07-2019-0129
|View full text |Cite
|
Sign up to set email alerts
|

The impact of telematics on the insurability of risks

Abstract: Purpose The purpose of this paper is to analyze the use of telematics in insurance and its consequences for the insurability of risks. Empirical results on monitoring policyholders or insured objects and its consequences for asymmetric information, as well as claims frequency and severity are discussed. Furthermore, potential future research questions that arise from the use of telematics in risk management and insurance are outlined. Design/methodology/approach The paper systematically reviews existing stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 56 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…If a young female driver manages to drive with care, this will be reflected in her premium, and she may not just be discriminated against on the basis of age. 99 Barry and Charpentier also make the case that the behavioral data gathered by telematics devices are more reliable than demographic data. 100 However, telematics and the associated data do bring with them more general fairness issues around surveillance, autonomy, and privacy.…”
Section: Resultsmentioning
confidence: 99%
“…If a young female driver manages to drive with care, this will be reflected in her premium, and she may not just be discriminated against on the basis of age. 99 Barry and Charpentier also make the case that the behavioral data gathered by telematics devices are more reliable than demographic data. 100 However, telematics and the associated data do bring with them more general fairness issues around surveillance, autonomy, and privacy.…”
Section: Resultsmentioning
confidence: 99%
“…Arumugam and Bhargavi (2019) describe a PHYD payment approach based on risk scores at a theoretical level, but they do not discuss any real case study examples. Eling and Kraft (2020) analyze the use of telematics in insurance and conclude that the reduction of information asymmetries, as well as the possibility of carrying out more accurate risk pooling, improves the insurability of risks; however, they stress the need for further research on loss frequency and severity in the context of telematics data. Geyer et al (2020) analyze a telematics data set with detailed information about driving behavior (speed, distance driven, and road type) in pay‐as‐you‐drive (PAYD) contracts that are based on distance driven and road type.…”
Section: Near‐miss Telematics and Usage‐based Insurancementioning
confidence: 99%
“…Hynes and Dickey (2008) found that even the rate of change of acceleration had an influence on rear‐impact vehicle collisions. We refer the reader to Eling and Kraft (2020; Table ) where they can find an updated, exhaustive and systematic summary of existing model approaches in telematics insurance.…”
Section: Near‐miss Telematics and Usage‐based Insurancementioning
confidence: 99%
“…[3] described the partnership of a system integrator and auto insurers based on the use of telematic devices, which in turn created a profitable business venture. This has opened an avenue for a number of data mining [30] and risk modeling approaches [31] based on the close ties between system integrators and the risk and contract management departments of insurers.…”
Section: The Dissection Of Relationships Among Main Stakeholdersmentioning
confidence: 99%